2016
DOI: 10.1253/circj.cj-16-0780
|View full text |Cite
|
Sign up to set email alerts
|

Diuretic Action of Sodium-Glucose Cotransporter 2 Inhibitors and Its Importance in the Management of Heart Failure

Abstract: Primarily, the sodium-glucose cotransporter 2 (SGLT2) inhibitors suppress the cotransport of glucose and sodium from the tubular lumen of the proximal tubules to the blood, and excrete glucose into the urine. Therefore, glucose and caloric balances become negative, reducing both the blood glucose level and insulin secretion. On the other hand, the proximal tubular fluid, constituted with low chloride concentration because of SGLT2 inhibition, is transferred to the loop of Henle. Under low chloride conditions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 26 publications
0
29
0
4
Order By: Relevance
“…Zinman et al reported that empagliflozin, one of the SGLT2 inhibitors, reduced the risk of major adverse cardiovascular events in patients with type 2 diabetes at high risk for cardiovascular events, 12 and in a report by Kimura, it was theorised that this cardioprotective action is related to diuretic action. 13 In addition, Wanner et al reported that empagliflozin is associated with slower progression of kidney disease and lower rates of clinically relevant renal events than the placebo when added to standard medical care. 14 Similar to the heart and kidney findings in that study, the suppression of diabetic retinopathy might also occur when SGLT2 inhibitors are added to the standard medical care.…”
Section: Discussionmentioning
confidence: 99%
“…Zinman et al reported that empagliflozin, one of the SGLT2 inhibitors, reduced the risk of major adverse cardiovascular events in patients with type 2 diabetes at high risk for cardiovascular events, 12 and in a report by Kimura, it was theorised that this cardioprotective action is related to diuretic action. 13 In addition, Wanner et al reported that empagliflozin is associated with slower progression of kidney disease and lower rates of clinically relevant renal events than the placebo when added to standard medical care. 14 Similar to the heart and kidney findings in that study, the suppression of diabetic retinopathy might also occur when SGLT2 inhibitors are added to the standard medical care.…”
Section: Discussionmentioning
confidence: 99%
“…These include: (a) diuretic and natriuretic effects leading to reduced plasma volume and thus cardiac preload; (b) greater reduction in extracellular fluid volume compared with that in blood volume through electrolyte‐free water clearance (as opposed to other diuretics); (c) BP lowering leading to reduced cardiac afterload and improved arterial compliance; (d) weight loss and reduced body fat; (e) shift in cardiac energy substrate from fat and glucose oxidation to more efficient ketone bodies; (f) anti‐inflammatory effects and reduced epicardial fat volume leading to reduced cardiac fibrosis and enhanced contractility; (g) reno‐protective effects such as improved salt and water homeostasis, reduced sympathetic activation and renin‐angiotensin‐aldosterone system (RAAS) activity (note that increased sodium reabsorption can lead to reduced delivery of sodium chloride to the macula densa, resulting in glomerular hyperfiltration. By reducing sodium reabsorption at the proximal tubules, SGLT‐2 inhibitors restore the tubuloglomerular feedback mechanism by delivering more sodium chloride to the macula densa, resulting in vasoconstriction of afferent arterioles, reduction of hyperfiltration and normalization of transglomerular perfusion pressures, which complement the vasodilation of efferent arterioles by RAAS inhibitors for renoprotection); (h) increase in haematocrit with improved oxygen delivery at tissue level; and (i) inhibition of sodium‐hydrogen exchanger (NHE) in the heart and vasculature (NHE1 isoform) and the kidneys (NHE3 isoform), which are implicated in sodium retention, cardiac hypertrophy, injury, fibrosis (leading to the progression of HF) and pathogenesis of diabetic nephropathy …”
Section: Potential Mechanisms Mediating the Cardiorenal Benefits Of Smentioning
confidence: 99%
“…Because SGLT-2 inhibitors require sufficient glomerular filtration and reabsorption of glucose and sodium by the proximal tubule to lower blood glucose and reduce body fluid volume, 5,12 their blood glucose-lowering effect and diuretic effect are thought to be impaired or eliminated in patients with poor renal function. 13 In the present study, SGLT-2 inhibition did not reduce HbA1c concentration, body weight, or systolic blood pressure.…”
Section: Discussionmentioning
confidence: 99%